Alterations in Notch signalling in skeletal muscles from mdx and dko dystrophic mice and patients with Duchenne muscular dystrophy. Issue 4 (26th February 2014) - Church, Jarrod E.; Trieu, Jennifer; Chee, Annabel; Naim, Timur; Gehrig, Stefan M.; Lamon, Séverine; Angelini, Corrado; Russell, Aaron P.; Lynch, Gordon S.
New Findings What is the central question of this study? The Notch signalling pathway plays an important role in muscle regeneration, and activation of the pathway has been shown to enhance muscle regeneration in aged mice. It is unknown whether Notch activation will have a similarly beneficial effect on muscle regeneration in the context of Duchenne muscular dystrophy (DMD). What is the main finding and its importance? Although expression of Notch signalling components is altered in both mouse models of DMD and in human DMD patients, activation of the Notch signalling pathway does not confer any functional benefit on muscles from dystrophic mice, suggesting that other signalling pathways may be more fruitful targets for manipulation in treating DMD. Abstract In Duchenne muscular dystrophy (DMD), muscle damage and impaired regeneration lead to progressive muscle wasting, weakness and premature death. The Notch signalling pathway represents a central regulator of gene expression and is critical for cellular proliferation, differentiation and apoptotic signalling during all stages of embryonic muscle development. Notch activation improves muscle regeneration in aged mice, but its potential to restore regeneration and function in muscular dystrophy is unknown. We performed a comprehensive examination of several genes involved in Notch signalling in muscles from dystrophin‐deficient mdx and dko (utrophin‐ and dystrophin‐null) mice and DMD patients. A reduction of Notch1 and Hes1 mRNA in tibialis anterior muscles of dko mice and quadriceps muscles of DMD patients and a reduction of Hes1 mRNA in the diaphragm of the mdx mice were observed, with other targets being inconsistent across species. Activation and inhibition of Notch signalling, followed by measures of muscle regeneration and function, were performed in the mouse models of DMD. Notch activation had no effect on functional regeneration in C57BL/10, mdx or dko mice. Notch inhibition significantly depressed the frequency–force relationship in regenerating muscles of C57BL/10 and mdx mice after injury, indicating reduced force at each stimulation frequency, but enhanced the frequency–force relationship in muscles from dko mice. We conclude that while Notch inhibition produces slight functional defects in dystrophic muscle, Notch activation does not significantly improve muscle regeneration in murine models of muscular dystrophy. Furthermore, the inconsistent expression of Notch targets between murine models and DMD patients suggests caution when making interspecies comparisons.